2018
DOI: 10.3389/fpsyg.2018.00795
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Updating, but Not Switching, Predict Developmental Dyslexia and Individual Variation in Reading Ability

Abstract: To elucidate the core executive function profile (strengths and weaknesses in inhibition, updating, and switching) associated with dyslexia, this study explored executive function in 27 children with dyslexia and 29 age matched controls using sensitive z-mean measures of each ability and controlled for individual differences in processing speed. This study found that developmental dyslexia is associated with inhibition and updating, but not switching impairments, at the error z-mean composite level, whilst con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Lastly, we observed that the average scores of monolingual and bilingual poor readers were generally lower than good readers in RAN. Given that children with dyslexia have been shown to have a delay in timing anticipation ( Pagliarini et al, 2020 ), inhibition control ( Reiter et al, 2005 ; Doyle et al, 2018 ), and RAN ( Carioti et al, 2022a ), it will be worth examining these observed trends further. There were no differences between monolingual and bilingual children in the language-independent tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, we observed that the average scores of monolingual and bilingual poor readers were generally lower than good readers in RAN. Given that children with dyslexia have been shown to have a delay in timing anticipation ( Pagliarini et al, 2020 ), inhibition control ( Reiter et al, 2005 ; Doyle et al, 2018 ), and RAN ( Carioti et al, 2022a ), it will be worth examining these observed trends further. There were no differences between monolingual and bilingual children in the language-independent tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Executive functioning, particularly inhibition control, has an essential role in anticipation. Children with dyslexia show impairments in inhibition control ( Reiter et al, 2005 ; Doyle et al, 2018 ; Barbosa et al, 2019 ). Some studies report higher levels of inhibition control in bilinguals than in monolinguals, whereas other studies document comparable performance ( Arizmendi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that some studies exploring EF and reading comprehension have found no correlation between the two, or only between certain EFs ( Pennington et al, 1993 ; Nydén et al, 1999 ; Willcutt et al, 2001 , 2005 , 2010 ; Jeffries and Everatt, 2004 ; Cain, 2006 ; Bental and Tirosh, 2007 ; Altemeier et al, 2008 ; Tiffin-Richards et al, 2008 ; de Jong et al, 2009 ; Menghini et al, 2010 ; Gooch et al, 2011 ; Christopher et al, 2012 ; Peng et al, 2013 ; Varvara et al, 2014 ; Moura et al, 2015 , 2017 ; Wang and Yang, 2015 ). However, the inconsistency in the research has been hypothesized to be due to several factors, including group classification difficulties, theoretical definition inconsistencies, and task impurity ( Doyle et al, 2018 ). Lastly, although some developmental theories agree that speed of processing abilities is part of EF ( Anderson and Reidy, 2012 ), this view is still under debate in the scientific community ( Gordon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed two aspects of executive function; response inhibition and verbal fluency. We assessed response inhibition using a computerised colour-naming Stroop task ( Balota et al, 2010 ; Doyle, Smeaton, Roche, & Boran, 2018 ), presented using E-prime ® . Participants were presented with a series of words and asked to name the colour of ink in which they were presented.…”
Section: Methodsmentioning
confidence: 99%